Population-based survey of HIV sero-status and vertical transmission among naive pregnant women in Sokoto, Nigeria - Buseri, Fiekumo Igbida; Okonkwo, Charity Ngozi (Asian Journal of Medical Sciences, 2014)
Background: This study aims at investigating the seroprevalence of HIV infection among status naive pregnant women and probable vertical transmission in Sokoto, Nigeria. Materials and Methods: This cross-sectional study examined 13,026 apparently healthy pregnant women aged between 14 and 45 years and 312 mother-baby pairs in 4 different hospital settings in Sokoto State, North West, Nigeria between March, 2011 and February, 2013. The babies were aged between 8 and 16 months. HIV screening was performed using qualitative rapid tests and ELISA and HIV-DNA polymerase chain reaction (PCR) techniques. Measurement of CD4+ T-lymphocytes was carried out by the BD FACScount System. All seropositive pregnant women were immediately placed on triple antiretroviral therapy (ART) throughout the duration of the pregnancy and beyond. Results: An overall 2.4% prevalence of HIV-1 infection among the pregnant women and 20.5% incident of mother-to-child transmission were found. Of the seropositive pregnant women, 75.0% were full-time house wives, 13.8% and 11.2% were traders and civil servants respectively; of which, 70.2% were within the ages of 14 and 27 years (youthful predominance). Pearson’s χ2analysis did not show any statistically significant difference in the Mean values in the 4 health facilities (χ2 =2.084, df=3, P-value=0.555). Similarly, no significant difference in HIV seropositivity in the demographic data of the pregnant women were observed (P>0.05). Infection was recorded in all age groups but there was no statistical significance between age groups and infection (P = 0.833). Of the 64 seropositive babies, 62 (92.5%) contracted HIV from antiretroviral therapy non-adherence mothers (χ2 =271.457, df=1, P<0.01), OR=1506.6 (95%CI=285.5-7950.4). Conclusion: This study found high prevalence of vertical transmission due to ART non-adherence. Intervention initiatives should, therefore, focus seriously on ART non-adherence. DOI: http://dx.doi.org/10.3126/ajms.v6i3.11530 Asian Journal of Medical Sciences Vol.6(3) 2015 49-57